2016
DOI: 10.3345/kjp.2016.59.11.s49
|View full text |Cite
|
Sign up to set email alerts
|

A novelBTKgene mutation, c.82delC (p.Arg28 Alafs*5), in a Korean family with X-linked agammaglobulinemia

Abstract: X-linked agammaglobulinemia (XLA) is a hereditary humoral immunodeficiency that results from Bruton’s tyrosine kinase (BTK) gene mutations. These mutations cause defects in B-cell development, resulting in the virtual absence of these lymphocytes from the peripheral circulation. Consequently, this absence leads to a profound deficiency of lg all isotypes, and an increased susceptibility to encapsulated bacterial infections. A 15-month-old Korean boy presented with recurrent sinusitis and otitis media after 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…Controversy still arises when considering BRAF V600E as a prognostic factor for pediatric LGG. While some researchers reported it to be a useful prognostic marker for PFS and OS [15], others reported it to be a useful prognostic factor for PFS, but not OS [11]. Our results are contradicting with this latter study since we reported BRAF V600E to be associated with a worse OS but not with PFS, something that could be due to the differences in age, tumor location and extent of surgical resection between both series of patients.…”
Section: Plos Onecontrasting
confidence: 99%
See 1 more Smart Citation
“…Controversy still arises when considering BRAF V600E as a prognostic factor for pediatric LGG. While some researchers reported it to be a useful prognostic marker for PFS and OS [15], others reported it to be a useful prognostic factor for PFS, but not OS [11]. Our results are contradicting with this latter study since we reported BRAF V600E to be associated with a worse OS but not with PFS, something that could be due to the differences in age, tumor location and extent of surgical resection between both series of patients.…”
Section: Plos Onecontrasting
confidence: 99%
“…Moreover, BRAF V600E mutation has been reported to abnormally up-regulate the MAPK signaling pathway [9,10]. Even though the BRAF V600E mutation responds unfavorably to conventional treatment, it represents a specific druggable target for personalized therapies with kinase inhibitors [11]. Moreover, CDKN2A has been previously shown to influence the response to treatment and outcome in BRAF V600E pediatric LGG [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…2,12 BTK mutations are found in 80% of patients with agammaglobulinemia. 13 This gene is located on X-chromosome at Xq21.3-Xq22, consisting of 19 exons and encompasses 37.5 kilo-base (kb) pair of human genome. 13 More than thousands of different mutations have been found in BTK, with missense mutations being the most frequent ones.…”
Section: Figurementioning
confidence: 99%
“…13 This gene is located on X-chromosome at Xq21.3-Xq22, consisting of 19 exons and encompasses 37.5 kilo-base (kb) pair of human genome. 13 More than thousands of different mutations have been found in BTK, with missense mutations being the most frequent ones. In line with this, the mutation that we described in our patient was a novel hemizygous missense mutation (c.428A>T, p.His143Leu).…”
Section: Figurementioning
confidence: 99%
“…While BTK deficiency can leave the body in a state of immunodeficiency (e.g., XLA), its upregulation may lead to autoimmune states, such as rheumatoid arthritis and systemic lupus erythematosus [19], as well as malignant states, notably B-cell malignancies [23], squamous cell carcinoma, and pancreatic cancer [24]. Hundreds of variants have been identified in the gene BTK from patients with XLA [25][26][27][28][29]18] which may explain phenotypic divergence in XLA [30]. Therefore, data are integrated to investigate genotype-phenotype interactions [31].…”
Section: X-linked Agammaglobulinemia (Bruton's Disease or Btk Deficiementioning
confidence: 99%